Looking back in anger? Putting in perspective the implementation of the Bologna process in Finnish and Portuguese higher education systems - Diogo, Sara (2021)
The analysis of policy implementation tends to focus on aspects related to legal frameworks, neglecting countries' cultural, political and institutional specifics. By comparing the implementation of the Bologna declaration in the Portuguese and Finnish higher education systems, this paper reflects on the different permutations of cultural-political changes wrought by the Europeanisation of higher education. Analysing policy implementation is thus considered essential to understand (effects of) policy change. This research adds to the literature on higher education policy the voices of practioners drawn from 47 interviews of system and institutional key actors in both countries. It is argued that while Portugal has a top-down tradition of policy implementation, Finland has been following a hybrid model of decision-making, combining top-down and bottom-up approaches. Empirical data challenge the importance of the national cultural dimension because, as is shown here, interviewees' perceptions differ more according to their role rather than their nationality. The apparent lack of visibility of national differences is explained by convergent trends such as managerialism and subsequent implications for the academic profession.